PERSPECTIVE ABOUT EFFECTIVENESS OF AUTOPSY AMONG PRIVATE MEDICAL STUDENTS’ OF FAISALABAD - Shirza Nadeem; Alaa Irshad; Muhammad Aslam (Journal of University Medical & Dental College, 2017)
ABSTRACT: Objective: To explore the knowledge, perception and attitude of the undergraduate medical students‟ of Faisalabad about autopsy. Design: The study design was cross-sectional. Methods: A structured and self-administered questionnaire was distributed among the 3rd year undergraduate medical students of the private medical institutes of Faisalabad. Result: Our study showed that 99% students comprehend the meaning of autopsy but only 55.9% know about the purpose and indication of autopsy. With regard to their perceptions, 42 % of the students believed autopsy to be contrary to their religious beliefs while significant number of students considered autopsy a disrespect and disfigurement to the human body. A majority of the students considered autopsy a great utility in society and medical education. Maximum number of students wanted to watch more autopsies as 55% have seen a total of 1-2 autopsies only. 67% suggested autopsy to be a compulsory part of the medical curriculum & did not want a replacement of the traditional autopsy with E-autopsy. However, only 46.6% of the students were of the view that fresh medical graduates should be posted as Casualty Medical Officers and deal with medicolegal cases. Conclusion: A better comprehension of the purpose of autopsy and its indications among the undergraduate medical students is required which demands an increased exposure of these students to autopsy.